Nominal wage adjustments and the composition of pay: New evidence from payroll data - Daniel Schaefer; Carl Singleton (Johannes Kepler University of Linz, Department of Economics, 2020)
We use representative payroll data from Great Britain to document novel facts about nominal wage adjustments, focusing on workers who stayed in the same firm and job from one year to the next. The richness of these data allows us to analyse basic pay and the other components of earnings, such as overtime and incentive pay, while accounting for hours worked. Weekly and hourly basic pay show signs of downward nominal rigidity, but non-basic pay components adjust more commonly. Unusually, these payroll-based data also report the wage rates of hourly-paid employees. A quarter of these workers typically see no change in their wage rates from one year to the next in the same job, and very few experience wage cuts. We exploit the employer-employee link in the data and find evidence of state-dependent pay setting, depending on the business cycle and whether firms are shrinking or expanding. Finally, we show that the basic and non-basic wages of new hires and existing employees are similarly flexible.
Keywords: E24; E32; J31; J33; 330; downward nominal wage rigidity; components of pay; hourly pay rates; hiring wages; allocative wages